FREQUENCY FEATURES OF CHRONIC NON-TUMORAL SIALADEN DISEASES OF THE POPULATION OF THE KHARKOV REGION - Lesovaya, I.G. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The information on frequency of chronic non-tumoral sialaden diseases of various groups of the population of the Kharkov region, according to the archive data of the specialized clinic of the Kharkov Medical Postgraduate Academy is submitted in this work.